2003
DOI: 10.1086/379293
|View full text |Cite
|
Sign up to set email alerts
|

Continuum and Emission-Line Properties of Broad Absorption Line Quasars

Abstract: We investigate the continuum and emission-line properties of 224 broad absorption line quasars (BALQSOs) with 0.9 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
330
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(381 citation statements)
references
References 43 publications
(82 reference statements)
42
330
4
1
Order By: Relevance
“…Willott et al (2003) observed 30 BAL quasars with 2 ≤ z ≤ 2.6 using the SCUBA camera at the JCMT. This sample was drawn from the SDSS Early DR BAL sample of Reichard et al (2003). Priddey et al (2003) performed SCUBA observations of 57 non-BAL quasars from the Large Bright Quasar Survey (LBQS; Hewett, Foltz & Chaffee 1995) in the redshift range 1.5 ≤ z ≤ 3; and Priddey et al (2007) observed 15 LBQS BAL QSOs with SCUBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willott et al (2003) observed 30 BAL quasars with 2 ≤ z ≤ 2.6 using the SCUBA camera at the JCMT. This sample was drawn from the SDSS Early DR BAL sample of Reichard et al (2003). Priddey et al (2003) performed SCUBA observations of 57 non-BAL quasars from the Large Bright Quasar Survey (LBQS; Hewett, Foltz & Chaffee 1995) in the redshift range 1.5 ≤ z ≤ 3; and Priddey et al (2007) observed 15 LBQS BAL QSOs with SCUBA.…”
Section: Discussionmentioning
confidence: 99%
“…Sanders et al 1988a), and much of the focus has been on the broad absorption line (BAL) class of QSOs. BAL QSOs exhibit broad troughs (∼2000-20 000 km s −1 wide) in their UV and optical spectra arising from resonance-line absorption in gas with high outflowing velocities up to 66 000 km s −1 (Lynds 1967;Foltz et al 1983;Weymann et al 1991;Hall et al 2002;Reichard et al 2003), comprising 26 per cent of QSOs (Trump et al 2006), and they come in three sub-types according to the visible absorption features: (1) high ionization BAL QSOs (HiBALs) show absorption in N V, Si IV and C IV; (2) low ionization BAL QSOs (LoBALs) contain all of the HiBAL absorption features plus absorption in Mg II and other low ionization species (Voit, Weymann & Korista 1993); and finally (3) the rarer FeLoBALs, which are LoBALs also exhibiting absorption from excited fine-structure levels or excited atomic terms of Fe II or Fe III (e.g. Hazard et al 1987;Becker et al 1997Becker et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Elvis 2000). LoBALQs are observed to have a redder continuum than HiBALQs (Weymann et al 1991;Boroson & Meyers 1992;Sprayberry & Foltz 1992;Reichard et al 2003;Gibson et al 2009), and are likely predominantly located at the parameter-space of the lowest He ii EW and the reddest αUV (BLH13). The increase in the CF of C iv BAL with decreasing He ii EW and redder αUV (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic fraction of quasars that are BALQs is estimated to be typically ∼20 per cent (Hewett & Foltz 2003;Reichard et al 2003;Knigge et al 2008;Gibson et al 2009;cf. Allen et al 2011), and ranges from ∼4 per cent in blue, strong He ii emission quasars, to ∼30 per cent in red, weak He ii emission quasars (Baskin, Laor & Hamann 2013, hereafter BLH13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation